2005
DOI: 10.1038/sj.eye.6702152
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of ICG-assisted ILM peeling and triamcinolone-assisted posterior vitreous removal in diffuse diabetic macular oedema

Abstract: Aim To compare the effect of indocyanine green (ICG)-assisted internal limiting membrane (ILM) peeling and triamcinolone acetonide-assisted posterior vitreous removal on visual acuity in patients with diffuse diabetic macular oedema (DMO). Methods In total, 24 patients with diffuse DMO who underwent pars plana vitrectomy were included in this study. In all, 11 patients (mean age 57 years) were performed ICGassisted ILM peeling; while 13 patients (mean age 54 years) underwent triamcinoloneassisted posterior vit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
1
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 11 publications
0
16
1
2
Order By: Relevance
“…There are three reports of ICG use in patients undergoing surgery for diabetic macular oedema. Two showed a favourable safety profile, 44,45 whereas one showed visual field defects, 42 making it difficult to draw a conclusion.…”
Section: Surgery For Diabetic Macular Oedemamentioning
confidence: 99%
“…There are three reports of ICG use in patients undergoing surgery for diabetic macular oedema. Two showed a favourable safety profile, 44,45 whereas one showed visual field defects, 42 making it difficult to draw a conclusion.…”
Section: Surgery For Diabetic Macular Oedemamentioning
confidence: 99%
“…In an exponentially increasing number of case series studies and nonrandomized comparative studies, IVTA has been used for the treatment of BRVO [80,81,82,83,84,85,86,87,88,89,90,91,92,251]. Özkiris et al [86] evaluated the efficacy of IVTA injection on persistent macular edema in BRVO that failed to respond to previous laser photocoagulation.…”
Section: Clinical Studies: Ta As Drug Treatment For Macular Edemamentioning
confidence: 99%
“…The removal of the ILM during macular surgery in elderly patients is generally done to enhance the surgical outcome. 15,16,20 Removal of the ILM was expected to reduce the recurrence rates by limiting the myofibroblasts proliferation, consequently minimizing the development of a recurrent ERM. Researches have also demonstrated that the surgical outcome is better and ERM recurrence is significantly lower in elderly ERM patients undergoing ILM peeling compared with those without ILM peeling.…”
Section: Discussionmentioning
confidence: 99%